Science and Whig Manners - Bord, Joe. author. aut Link
IX, 213 p. 1 illus.
Keywords: Approaching the intersection of politics and science from the perspective of political history, this book looks at how nineteenth-century British Whigs used the themes of natural science to signal their identities, and how their devotion to a culture of liberality helped to define them. Offers a fresh take on a central theme in Victorian politics.